Competitive Strategies of Office Furniture Retailing An Exploratory Study in the Territory of Klang Valley - Saw, Eng Guan (2010)
Kuala Lumpur which is in the territory of Klang Valley has gone through a vast transformation the last decade and shopping experience has never been the same. Small retailers are facing a tremendous challenge with the emergence of organized specialty stores and big box super store such as IKEA. The standard of living, the lifestyles and consumer behavior has gone through a cycle of evolution. Consumer today is more selective and choosy of the goods and services they buy and from who they buy from. Thus, for a retailer to remain competitive and achieve profitability, it is vital that they possess distinctive competitive advantages that will assist them to excel in the market place. The objective of this paper is to look into the current dimensions of competitive advantage possess by the five sample office furniture retail stores and to develop a framework to analyze the applicability of Porter‟s dichotomy of price and differentiation as a strategy model to achieve competitive advantage. In order to derive the basic dimensions of competitive advantages in the furniture retail business, the employees of the top five office furniture retailers in Klang Valley have been surveyed. A total of 100 office furniture consumers have also been interviewed to examine and define the dimensions of retail store competitive advantage. The result of the survey analysis will showed that the key of omissions often lies in the strategy planning of managers in the focusing of important competitive advantage dimension that contribute to the success of retailing.